The Role of Tetraether Lipid Composition in the Adaptation of Thermophilic Archaea to Acidity - Boyd, Eric; Hamilton, Trinity; Wang, Jinxiang; He, Liu; Zhang, Chuanlun (Frontiers in Microbiology, 2013)
Diether and tetraether lipids are fundamental components of the archaeal cell membrane. Archaea adjust the degree of tetraether lipid cyclization in order to maintain functional membranes and cellular homeostasis when confronted with pH and/or thermal stress. Thus, the ability to adjust tetraether lipid composition likely represents a critical phenotypic trait that enabled archaeal diversification into environments characterized by extremes in pH and/or temperature. Here we assess the relationship between geochemical variation, core- and polar-isoprenoid glycerol dibiphytanyl glycerol tetraether (C-iGDGT and P-iGDGT, respectively) lipid composition, and archaeal 16S rRNA gene diversity and abundance in 27 geothermal springs in Yellowstone National Park (YNP), Wyoming. The composition and abundance of C-iGDGT and P-iGDGT lipids recovered from geothermal ecosystems were distinct from surrounding soils, indicating that they are synthesized endogenously. With the exception of GDGT-0 (no cyclopentyl rings), the abundances of individual C-iGDGT and P-iGDGT lipids were significantly correlated. The abundance of a number of individual tetraether lipids varied positively with the relative abundance of individual 16S rRNA gene sequences, most notably crenarchaeol in both the core and polar GDGT fraction and sequences closely affiliated with Candidatus Nitrosocaldus yellowstonii. This finding supports the proposal that crenarchaeol is a biomarker for nitrifying archaea. Variation in the degree of cyclization of C- and P-iGDGT lipids recovered from geothermal mats and sediments could best be explained by variation in spring pH, with lipids from acidic environments tending to have, on average, more internal cyclic rings than those from higher pH ecosystems. Likewise, variation in the phylogenetic composition of archaeal 16S rRNA genes could best be explained by spring pH. In turn, the phylogenetic similarity of archaeal 16S rRNA genes was significantly correlated with